2019
DOI: 10.1002/mp.13421
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Deriving ventilation imaging from 4DCT by deep convolutional neural network

Abstract: Purpose Ventilation images can be derived from four‐dimensional computed tomography (4DCT) by analyzing the change in HU values and deformable vector fields between different respiration phases of computed tomography (CT). As deformable image registration (DIR) is involved, accuracy of 4DCT‐derived ventilation image is sensitive to the choice of DIR algorithms. To overcome the uncertainty associated with DIR, we develop a method based on deep convolutional neural network (CNN) to derive ventilation images dire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Neural networks have also been proposed as a means of generating ventilation images. 21 The majority of described CT ventilation methods have been applied to 4DCT data; however, Eslick et al 23 recently demonstrated improved accuracy of CT ventilation images using breath-hold CTs for ventilation image calculation. Although these more recently proposed methods of calculating CT ventilation are in their nascent state, early results suggest promise in overcoming some of the challenges associated with conventional CT-ventilation calculation methodologies.…”
Section: Calculation Methodsologies Of Ct-based Ventilation Imagingmentioning
confidence: 99%
“…Neural networks have also been proposed as a means of generating ventilation images. 21 The majority of described CT ventilation methods have been applied to 4DCT data; however, Eslick et al 23 recently demonstrated improved accuracy of CT ventilation images using breath-hold CTs for ventilation image calculation. Although these more recently proposed methods of calculating CT ventilation are in their nascent state, early results suggest promise in overcoming some of the challenges associated with conventional CT-ventilation calculation methodologies.…”
Section: Calculation Methodsologies Of Ct-based Ventilation Imagingmentioning
confidence: 99%
“…Convolutional neural networks (CNNs), which is the main DL tool to handle medical images, can utilize spatial and structural information effectively duo to the ability of taking two‐dimensional (2D) or three‐dimensional (3D) information as input. More recently, Zhong et al employed a deep CNNs with nine layers to derive ventilation maps from 4DCT, which can well illustrate the feasibility of the DL method in generating pulmonary ventilation images. However, the main limitation in that study is the label data is the ventilation images calculated from HU method, which highly depends on the accuracy of the employed DIR algorithm.…”
Section: Introductionmentioning
confidence: 98%
“…In the proposed framework, image processing, especially CT contrast enhancement, plays a crucial role in the perfusion synthesis. Before our study, most of the existing CT based pulmonary function studies used ( 24 , 36 , 37 ) deformable image registration (DIR) algorithms to derive ventilation in view of that both pulmonary ventilation and perfusion are correlated with the radiotherapy-induced pneumonitis ( 38 ). However, the accuracy of DIR based lung function mapping methods may be variable in different DIR algorithms and settings ( 39 ).…”
Section: Discussionmentioning
confidence: 99%